Nickel(ii)-catalyzed direct olefination of benzyl alcohols with sulfones with the liberation of H-2 - Landge, Vinod G.; Yadav, Vinita; Subaramanian, Murugan; Dangarh, Pragya; Balaraman, Ekambaram (Chemical Communications, 2019)
A nickel(II)-catalyzed direct olefination of benzyl alcohols with sulfones to access various terminal and internal olefins with the liberation of hydrogen gas is reported.